REDEFINING THE ROLE OF TEACHERS IN THE DIGITAL ERA 5.0: IMPLEMENTING CREATIVE PEDAGOGY IN MUSIC ARRANGEMENT COURSES - Sena Radya Iswara Samino; Dedy Setyawan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The rapid development of artificial intelligence in music software during the Society 5.0 era has significantly transformed how students approach music arrangement. Automated features and generative systems enable students to produce sonically complex works in a short time. However, this condition also gives rise to a phenomenon known as the illusion of competence, in which convincing musical output is not necessarily accompanied by a solid understanding of underlying musical structures. This study aims to describe how the instructor's role needs to be redefined through a creative pedagogical approach in response to these changes. The research employs a descriptive qualitative method, combining literature review and classroom observation of arrangement learning supported by music software. The findings indicate that instructors can no longer function merely as technical trainers. Instead, they need to act as post-algorithmic aesthetic validators, guiding students to reflect on and justify their musical decisions. The study highlights that integrating AI into music education may accelerate sound production while simultaneously shortening the development of musical reasoning, if not balanced by critical pedagogical intervention. Redefining the instructor’s role, therefore, becomes essential to ensure that arrangement learning cultivates musical awareness rather than merely operational proficiency with digital systems.